Changes in selected physiological parameters following a training block of specific circuit training among national top-level basketball players - Tonan, B. A.; Gouthon, P. N,; Bio Nigan, I.; Akpatchi, R. V.; Nouatin, B. (International Journal of Exercise Science, 2020)
The study aims at measuring the effects of six weeks of specific circuit training (SCT) according to the 15-15 modality, on selected physiological parameters in national top-level basketball players. It was an intervention study, undertaken with 44 senior players randomly assigned to two groups depending on the program: intervention (IG: n = 22; SCT) and control (CG: n = 22; usual content of the defending champion team's), submitted to a six-week training block. The heart rate recovery at 1 (HRR1) and then 2 (HRR2) minutes, the double product (DP) and O2max were assessed prior to and at the end of the training period. As appropriate, the Student t-test on paired or independent samples, was used to compare measures and groups. At the end of the training period, the HRR1 decreased by 14.2% (p = 0.01) and 14.1% (p = 0.03) respectively in IG and CG. The mean HRR2 was higher in IG than in GC (63 ± 8 bpm versus 57 ± 6 bpm, p = 0.003) at the end of the training period. The variation of DP in IG was not significant (p = 0. 42) while it increased by 7.2% (p = 0.0005) in CG. The O2max increased by 6.5% (p ? 0. 001) in IG but not in CG (p = 0.50). The specific circuit training block in the 15-15 modality improved heart rate recovery at one minute and O2max, but had no effect on the double product in the basketball players studied.